Effects of zinc, selenium, iron, and copper on COVID-19 patients and relationship with oxidative stress-induced DNA damage - Sertöz, Seçil; Karabağ, Funda; Karagöz, Alper (The Journal of Infection in Developing Countries, 2026)
Introduction: Coronavirus disease 2019 (COVID-19) is a highly contagious and pathogenic viral infection caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which emerged in Wuhan, China, and subsequently spread globally. Methodology: Individuals were divided into categories (positive and control) according to their polymerase chain reaction (PCR) test results, gender, and age (< 36, 37–46, and 47–56 years). Oxidative stress parameters including 8-hydroxydeoxyguanosine (8-OHdG), total oxidative stress capacity (TOS), and total antioxidant capacity (TAS) in serum samples were investigated by enzyme linked immunosorbent assay (ELISA). Trace elements iron, zinc, copper, and selenium were measured with the Thermo Scientific ICAP-Q ICP-MS device. Results: Statistical analyses revealed significant differences in 8-OHdG, TOS, and TAS levels between the control and COVID-19 positive groups (p < 0.01). Men had higher 8-OHdG and TOS levels than women. Iron, zinc, copper, and selenium did not show a normal distribution in the COVID-19 group; and there was a significant difference in their levels between the control and COVID-19 groups (p < 0.05). There was an increase in oxidative DNA damage and a decrease in antioxidant status in COVID-19 positive individuals due to oxidative stress parameter values. Conclusions: The results will contribute significantly to the current knowledge. Additional assessment of various oxidative stress and antioxidant markers and the use of alternative molecular testing systems are mandatory to further elucidate the effect of COVID-19 on oxidative stress. This study may have a pioneering status in the literature as such a comparative study has not been conducted before.